Difference between revisions of "009B Sample Final 1, Problem 2"

From Math Wiki
Jump to navigation Jump to search
 
(One intermediate revision by the same user not shown)
Line 1: Line 1:
 
<span class="exam"> We would like to evaluate
 
<span class="exam"> We would like to evaluate
:::::<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg).</math>
+
::<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg).</math>
  
::<span class="exam">a) Compute <math style="vertical-align: -15px">f(x)=\int_{-1}^{x} \sin(t^2)2t\,dt.</math>
+
<span class="exam">(a) Compute &nbsp;<math style="vertical-align: -15px">f(x)=\int_{-1}^{x} \sin(t^2)2t\,dt.</math>
  
::<span class="exam">b) Find <math style="vertical-align: -5px">f'(x).</math>
+
<span class="exam">(b) Find &nbsp;<math style="vertical-align: -5px">f'(x).</math>
  
::<span class="exam">c) State the Fundamental Theorem of Calculus.
+
<span class="exam">(c) State the Fundamental Theorem of Calculus.
  
::<span class="exam">d) Use the Fundamental Theorem of Calculus to compute&thinsp; <math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg)</math> &thinsp;without first computing the integral.
+
<span class="exam">(d) Use the Fundamental Theorem of Calculus to compute &nbsp;<math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t\,dt\bigg)</math>&nbsp; without first computing the integral.
 
 
::<span class="exam">d) Use the Fundamental Theorem of Calculus to compute&thinsp; <math style="vertical-align: -15px">\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2tdt\bigg)</math> &thinsp;without first computing the integral.
 
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|How would you integrate <math>\int e^{x^2}2x~dx?</math>
+
|How would you integrate &nbsp;<math>\int e^{x^2}2x~dx?</math>
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: -1px">u</math>-substitution. Let <math style="vertical-align: 0px">u=x^2.</math> Then, <math style="vertical-align: 0px">du=2xdx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;You could use &nbsp;<math style="vertical-align: -1px">u</math>-substitution.  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;Let &nbsp;<math style="vertical-align: 0px">u=x^2.</math>&nbsp; Then, &nbsp;<math style="vertical-align: 0px">du=2xdx.</math>
 
|-
 
|-
 
|
 
|
::So, we get <math style="vertical-align: -14px">\int e^u~du=e^u+C=e^{x^2}+C.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;So, we get &nbsp;<math style="vertical-align: -14px">\int e^u~du=e^u+C=e^{x^2}+C.</math>
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 31: Line 32:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We proceed using <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=t^2.</math> Then, <math style="vertical-align: 0px">du=2t\,dt.</math>
+
|We proceed using &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 +
|-
 +
|Let &nbsp;<math style="vertical-align: 0px">u=t^2.</math>&nbsp; Then, &nbsp;<math style="vertical-align: 0px">du=2t\,dt.</math>  
 
|-
 
|-
 
|Since this is a definite integral, we need to change the bounds of integration.  
 
|Since this is a definite integral, we need to change the bounds of integration.  
 
|-
 
|-
|Plugging our values into the equation <math style="vertical-align: -4px">u=t^2,</math> we get <math style="vertical-align: -5px">u_1=(-1)^2=1</math> and <math style="vertical-align: -3px">u_2=x^2.</math>
+
|Plugging our values into the equation &nbsp;<math style="vertical-align: -4px">u=t^2,</math>&nbsp; we get  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">u_1=(-1)^2=1</math>&nbsp; and &nbsp;<math style="vertical-align: -3px">u_2=x^2.</math>
 
|}
 
|}
  
Line 44: Line 49:
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
f(x) & = & \displaystyle{\int_{-1}^{x} \sin(t^2)2t~dt}\\
 
f(x) & = & \displaystyle{\int_{-1}^{x} \sin(t^2)2t~dt}\\
 
&&\\
 
&&\\
Line 61: Line 66:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|From part (a), we have <math style="vertical-align: -5px">f(x)=-\cos(x^2)+\cos(1).</math>
+
|From part (a), we have &nbsp;<math style="vertical-align: -5px">f(x)=-\cos(x^2)+\cos(1).</math>
 
|}
 
|}
  
Line 67: Line 72:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|If we take the derivative, we get <math style="vertical-align: -5px">f'(x)=\sin(x^2)2x,</math> since <math style="vertical-align: -5px">\cos(1)</math> is just a constant.
+
|If we take the derivative, we get &nbsp;<math style="vertical-align: -5px">f'(x)=\sin(x^2)2x,</math>&nbsp; since &nbsp;<math style="vertical-align: -5px">\cos(1)</math>&nbsp; is a constant.
 
|}
 
|}
  
Line 77: Line 82:
 
|The Fundamental Theorem of Calculus has two parts.  
 
|The Fundamental Theorem of Calculus has two parts.  
 
|-
 
|-
|'''<u>The Fundamental Theorem of Calculus, Part 1</u>'''
+
|'''The Fundamental Theorem of Calculus, Part 1'''
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;Let &nbsp;<math>f</math>&nbsp; be continuous on &nbsp;<math style="vertical-align: -5px">[a,b]</math>&nbsp; and let &nbsp;<math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt.</math>
:Let <math>f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt.</math>
 
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;Then, &nbsp;<math style="vertical-align: 0px">F</math>&nbsp; is a differentiable function on &nbsp;<math style="vertical-align: -5px">(a,b)</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">F'(x)=f(x).</math>
:Then, <math style="vertical-align: 0px">F</math> is a differentiable function on <math style="vertical-align: -5px">(a,b)</math> and <math style="vertical-align: -5px">F'(x)=f(x).</math>  
 
 
|}
 
|}
  
Line 89: Line 92:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|'''<u>The Fundamental Theorem of Calculus, Part 2</u>'''
+
|'''The Fundamental Theorem of Calculus, Part 2'''
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;Let &nbsp;<math>f</math>&nbsp; be continuous on &nbsp;<math>[a,b]</math>&nbsp; and let &nbsp;<math style="vertical-align: 0px">F</math>&nbsp; be any antiderivative of &nbsp;<math>f.</math>
:Let <math>f</math> be continuous on <math>[a,b]</math> and let <math style="vertical-align: 0px">F</math> be any antiderivative of <math>f.</math>
 
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;Then, &nbsp;<math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a).</math>
:Then, <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a).</math>
 
 
|}
 
|}
  
Line 104: Line 105:
 
|-
 
|-
 
|
 
|
::<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t~dt\bigg)\,=\,\sin(x^2)2x.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{d}{dx}\bigg(\int_{-1}^{x} \sin(t^2)2t~dt\bigg)\,=\,\sin(x^2)2x.</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|'''(a)''' &nbsp;<math>f(x)=-\cos(x^2)+\cos(1)</math>
+
|&nbsp; &nbsp;'''(a)''' &nbsp; &nbsp;<math>f(x)=-\cos(x^2)+\cos(1)</math>
|-
 
|'''(b)''' &nbsp;<math>f'(x)=\sin(x^2)2x</math>
 
|-
 
|'''(c)''' &nbsp;'''<u>The Fundamental Theorem of Calculus, Part 1</u>'''
 
|-
 
|&nbsp;&nbsp;Let <math>f</math> be continuous on <math style="vertical-align: -5px">[a,b]</math> and let <math style="vertical-align: -14px">F(x)=\int_a^x f(t)~dt</math>.
 
|-
 
|&nbsp;&nbsp;Then, <math style="vertical-align: 0px">F</math> is a differentiable function on <math style="vertical-align: -5px">(a,b)</math> and <math style="vertical-align: -5px">F'(x)=f(x)</math>. 
 
|-
 
|'''<u>The Fundamental Theorem of Calculus, Part 2</u>'''
 
 
|-
 
|-
|&nbsp;&nbsp;Let <math>f</math> be continuous on <math>[a,b]</math> and let <math style="vertical-align: 0px">F</math> be any antiderivative of <math>f</math>.
+
|&nbsp; &nbsp;'''(b)''' &nbsp; &nbsp;<math>f'(x)=\sin(x^2)2x</math>
 
|-
 
|-
|&nbsp;&nbsp;Then, <math style="vertical-align: -14px">\int_a^b f(x)~dx=F(b)-F(a)</math>.
+
|&nbsp; &nbsp;'''(c)''' &nbsp; &nbsp;See above
 
|-
 
|-
|'''(d)''' &nbsp;<math style="vertical-align: -5px">\sin(x^2)2x</math>
+
|&nbsp; &nbsp;'''(d)''' &nbsp; &nbsp;<math style="vertical-align: -5px">\sin(x^2)2x</math>
 
|}
 
|}
 
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:41, 10 April 2017

We would like to evaluate

(a) Compute  

(b) Find  

(c) State the Fundamental Theorem of Calculus.

(d) Use the Fundamental Theorem of Calculus to compute    without first computing the integral.

Foundations:  
How would you integrate  

       You could use  -substitution.

       Let    Then,  

       So, we get  


Solution:

(a)

Step 1:  
We proceed using  -substitution.
Let    Then,  
Since this is a definite integral, we need to change the bounds of integration.
Plugging our values into the equation    we get
         and  
Step 2:  
So, we have

       


(b)

Step 1:  
From part (a), we have  
Step 2:  
If we take the derivative, we get    since    is a constant.

(c)

Step 1:  
The Fundamental Theorem of Calculus has two parts.
The Fundamental Theorem of Calculus, Part 1
       Let    be continuous on    and let  
       Then,    is a differentiable function on    and  
Step 2:  
The Fundamental Theorem of Calculus, Part 2
       Let    be continuous on    and let    be any antiderivative of  
       Then,  
(d)  
By the Fundamental Theorem of Calculus, Part 1,

       


Final Answer:  
   (a)    
   (b)    
   (c)    See above
   (d)    

Return to Sample Exam